Modelling heat generation and transfer during cure of thermoset composites processed by resin transfer moulding (RTM) - Skordos, Alexandros A.; Maistros, George M.; Turmel, Denis J-P; Partridge, Ivana K. (Cranfield University, 1997)
The development of a heat transfer model for the curing stage of the RTM process is presented. Despite the intense interest in the modelling and simulation of this process the relevant work is currently limited to development of flow models of the filling stage. The principles of heat transfer modelling of composites cure have already been reported and applied to the autoclave process by many investigators. In the present investigation, the same concept is used for the implementation of Galerkin finite element approach to RTM curing. The mathematical basis of the resulting semidiscrete model is presented here and the temporal algorithm is described. The experimental mould, which will be used to evaluate and validate the model is also described.